2015
DOI: 10.1103/physrevd.91.014503
|View full text |Cite
|
Sign up to set email alerts
|

Dsη,ηsemileptonic decay form factors with disconnected quark loop contributions

Abstract: We calculate for the first time the form factors of the semileptonic decays of the Ds meson to η and η ′ using lattice techniques. As a by-product of the calculation we obtain the masses and leading distribution amplitudes of the η and η ′ mesons. We use N f = 2 + 1 non-perturbatively improved clover fermions on configurations with a lattice spacing a ∼ 0.075 fm. We are able to obtain clear signals for relevant matrix elements, using several noise reduction techniques, both for the connected and disconnected c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 42 publications
(285 reference statements)
3
49
0
Order By: Relevance
“…Lattice QCD data for G P can also be found in Refs. [76,78,80,84]. For the following discussion we recall that G P can be decomposed in the physical regime into…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…Lattice QCD data for G P can also be found in Refs. [76,78,80,84]. For the following discussion we recall that G P can be decomposed in the physical regime into…”
Section: Figmentioning
confidence: 99%
“…The results from Refs. [74][75][76] are obtained near the physical point or at the physical point. Recent calculations of G A as a function of Q 2 can be found in Refs.…”
Section: A Axial-vector Form Factor (Ga)mentioning
confidence: 99%
See 1 more Smart Citation
“…We found in our ensembles that the topological charge has zero expectation value, however, the second moment of the charge distribution might not be sampled fully correctly. While being a finite volume effect, this can lead to time independent contributions to the flavour-singlet correlation function [36,37]. As a consequence, the corresponding correlation functions do not decay to zero at large time separations.…”
Section: Pollution By Topological Effectsmentioning
confidence: 99%
“…Such constants present in correlation functions can be subtracted by fitting the appropriate functional form to the data [37]. However, we found that shifting the correlation functions -invented to cancel so-called thermal pollution in multi-hadron correlation functions [38] -subtracts the constant without the need of any additional input.…”
Section: Pollution By Topological Effectsmentioning
confidence: 99%